Living‐donor kidney transplantation in an end‐stage renal disease patient with situs inversus totalis: Three case reports. Issue 2 (22nd February 2019) - Ochi, Atsuhiko; Unagami, Kohei; Akanuma, Takafumi; Inoue, Takahiro; Okada, Daigo; Fan, Bo; Suzuki, Tomo; Abe, Hirokazu; Okumi, Masayoshi; Ishida, Hideki; Tanabe, Kazunari
Abstract : Introduction: Only few cases of renal dysfunction in patients with situs inversus totalis have been reported. Thus, studies on kidney transplantation in patients with this condition are still limited. Case presentation: We present three cases of end‐stage renal disease patients with situs inversus totalis: a 30‐year‐old man, 21‐year‐old woman, and 31‐year‐old man. Each left living‐donor kidney was transplanted in the right iliac fossa in the usual way. Because of the anatomical reversal and right external iliac vein being deep, the internal iliac vein was cut for venous anastomosis in one patient. Another one patient developed temporary congestive kidney, which was speculated to be due to poor blood flow in the renal vein. All recipients could be weaned off dialysis, with stable allograft function. Conclusion: Kidney transplantation in patients with situs inversus totalis is the same as anatomical normal cases, except that attention is paid to venous anastomosis.